1992
DOI: 10.1073/pnas.89.18.8443
|View full text |Cite
|
Sign up to set email alerts
|

Genomic structure and chromosomal mapping of the mouse N-cadherin gene.

Abstract: N-cadherin is a member of the cadherin cellcell adhesion receptor family that includes P-, E-, and R-cadherin and liver cell adhesion molecule (L-CAM). In this study, we determined the structure of the mouse N-cadherin gene by analyzing overlapping genomic clones obtained from a mouse genomic library. This gene consists of 16 exons that disperse over >200 kilobases of genomic DNA. This large size of the N-cadherin gene, compared with its cDNA (4.3 kilobases), is ascribed to the fact that the first and second i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…1 A) and all of the other genes characterized thus far in this cluster are interrupted by two introns. This intron͞exon organization is typical of classic cadherin genes (7)(8)(9)(10)(11). By contrast, the six ectodomains of every member of the human protocadherin ␣, ␤, and ␥ proteins are encoded in a single, unusually large exon (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 A) and all of the other genes characterized thus far in this cluster are interrupted by two introns. This intron͞exon organization is typical of classic cadherin genes (7)(8)(9)(10)(11). By contrast, the six ectodomains of every member of the human protocadherin ␣, ␤, and ␥ proteins are encoded in a single, unusually large exon (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Studies of the genomic organization of a number of classic cadherin genes revealed that the DNA sequences encoding individual ectodomains are interrupted by two introns (7)(8)(9)(10)(11)). An example of this is provided by human Ksp-cadherin (CDH16) gene (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reeler may act in the N-cadherin regulatory pathway causing either an over-or early expression, resulting in the ectopic positioning of the earliest postmitotic deep-layer neurons. Nevertheless the reeler mutation (mapped to chromosome 5; Goffinet, 1992) is not a hypermorphic mutation of the N-cadherin gene itself (mapped to chromosome 18; Miyatani et al, 1992). The cerebellum of reeler mutants is characterized by the malpositioning and loss of Purkinje neurons and a substantial reduction in the granule cell population (Goffinet, 1984;Heckroth et al, 1989;Goffinet, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…A description of the probes and RFLPs for the loci linked to Evi5, Evi5-rs1 and Evi5-rs2 have been described. These loci include ®broblast growth factor 5 (Fgf5), growth factor independence 1 (G®1) and crystallin beta B2 (Crybb2) on chromosome 5 (Benovic et al, 1991;Bell et al, 1995;Hulsebos et al, 1995); interferon gamma (Igf), glioma associated oncogene (Gli) and avian erythroblastosis oncogene B3 (Erbb3) on chromosome 10 (Justice et al, 1990;Copeland et al, 1995); and tumor progression locus 2 (Tpl2) and cadherin 2 (Cdh2) on chromosome 18 (Justice et al, 1992;Miyatani et al, 1992). Recombination distances were calculated as described (Green, 1981) using the computer program SPRETUS MADNESS.…”
Section: Interspeci®c Backcross Mappingmentioning
confidence: 99%